Koperasi dan Akselerasi UMKM di Kota Balikpapan - Indrayani, Indrayani; Nurlia, Nurlia (Universitas Batanghari Jambi, 2024)
Cooperatives and the acceleration of SMEs in Balikpapan City play a significant role in advancing the local economy. Through the cooperative model, SMEs gain access to business capital, training, joint marketing, and collective purchasing, enabling them to compete effectively in a competitive market. Collaboration among cooperatives is key to success, while the utilization of digital technology accelerates SME growth. Support from the local government and the private sector is crucial in stimulating growth and innovation in this sector. Despite facing various challenges, cooperatives and SMEs in Balikpapan have great potential to continue to grow and become drivers of an inclusive and sustainable economy at the local and regional levels